Big Mac Trademark Dispute in the European Union Between Mcdonald's And Supermac's - Iswardhana, Muhammad Ridha (Institute for Law and Economics Studies, 2026)
The dispute between the American fast food giant McDonald's and the Irish fast food chain Supermac’s over the Big Mac trademark in the European Union highlights important issues in trademark law and market protection. The conflict began in 2015 when Supermac's applied to register its name as a trademark for restaurant services in Europe, but McDonald's opposed the registration, claiming that the name